(untitled) (International scientific-electronic journal “Pioneering studies and theories”, 2025)
This article examines the strategic role of green innovation in strengthening industrial competitiveness amid accelerating global environmental transformation and rising sustainability requirements across international markets. The study analyzes how ecological modernization, resource-efficient technologies, and environmentally oriented organizational practices contribute to productivity growth, cost optimization, and long-term resilience of industrial enterprises. Special attention is given to the institutional drivers that shape green innovation adoption, including regulatory frameworks, public–private collaboration, financial incentives, and national innovation infrastructure. The research further explores economic tools that facilitate the integration of green technologies into industrial production, highlighting the importance of green financing mechanisms, ESG-aligned management systems, and capability-building programs. The findings indicate that green innovation strategies enable industries to achieve competitive advantages by reducing environmental risks, improving operational efficiency, expanding export potential, and meeting the increasingly stringent ecological standards of global value chains. However, the diffusion of green innovation is constrained by institutional gaps, limited access to sustainable finance, uneven technological readiness, and insufficient alignment between industrial and environmental policies. The article concludes that future development pathways must incorporate comprehensive institutional support, coordinated policy measures, and advanced innovation tools to ensure industrial sectors can transition toward sustainable growth and maintain competitiveness in a rapidly evolving global economy.